Resumption of Elective Surgery Following COVID-19 Outbreak, Guideline for Female Pelvic Medicine and Surgery - Zinat Ghanbari; Fatemeh Mostaan; Tahereh Eftekhar; Maryam Deldar; Nasrin Changizi; Khadijeh Adabi (Tehran University of Medical Sciences, 2020)
Division of Female Pelvic Medicine and Surgery, Department of Obstetrics and Gynecology, Emam Khomeini Hospital, Tehran University of medical sciences proposed a clinically relevant algorithm to guide appropriate decision making based on underlying risk stratification and resource utilization in order to resume elective surgeries, following COVID-19 pandemic crisis. The consequence of standardized decision-making factors and transparency of the principles will provide more assurance, consistency, and reliability on both sides, care providers and the patient. It also will decrease ethical dilemmas and moral criticism for surgeons. Eventually, this approach is applicable in any other disaster preparedness as a logical stratification of surgical indications for the female pelvic floor surgical procedures.